Degree of tumor shrinkage following neoadjuvant chemoradiotherapy: a potential predictor for complete pathological response in esophageal cancer?. Issue 6 (1st August 2014) - Voncken, F. E. M.; Jiang, H.; Kim, J.; Guindi, M.; Brierley, J.; Knox, J.; Liu, G.; Horgan, A. M.; Lister, J.; Darling, G.; Metser, U.; Wong, R. K. S.
Summary: Neoadjuvant chemoradiotherapy (CRT ) before surgery results in a pathological complete response (pCR ) rate in about 1/3 of the patients, which is correlated with survival. It was hypothesized that volumetric tumor response to CRT would correlate with outcomes. Patients who completed trimodality therapy, where planning, pre-, and post-CRT computed tomography scans were available, and pathology was reviewed by a central pathologist, were eligible for analysis. Absolute and relative tumor volume change pretreatment and post-treatment were correlated with pCR, locoregional recurrence (LRR ), disease-free survival, and overall survival. Fifty-six patients were analyzed. pCR was observed in 30% of patients. Median follow up was 20.3 (range 4–89) months. The 2- and 4-year overall survival was 61.3% (95% confidence interval [CI ]: 45–74) and 25.0% (95%CI : 11–41); proportion disease free was 32.1% (95% CI : 19–46) and 20.6% (9–36) at 2 and 4 years, respectively. The median relative volume reduction was 17% (95% CI : −24, −3%). Using 20% as the criteria, the proportion of patients with pCR of ≥20% versus <20% was 13/25 (52%) versus 4/31 (13%) for those who did not (odds ratio 7.3; 95% CI : 2–27). The LRR at 2 and 4 years were 29.5% (95% CI : 16–43) and 36.2% (95% CI : 23–50). The relative tumor reduction ≥20% was significantly correlated with LRR (hazard ratio 0.24; 95% CI : 0.07–0.8; p 0.02) at 2 and 4 years, respectively. Relative tumor volume reduction following CRT is correlated with pCR and LRR . Further investigations are warranted to examine the effect of volume change, alone or in conjunction with other factors as potential predictors for pathological response.